Numerical modelling of double integration with different data spacing: A Python-based approach - Priyanshi Mishra; Pramiti Tewari; Dhananjay Mishra; Pankaj Dumka (Mathematics and computational sciences, 2023)
In this article, an attempt has been made to model the process of double integration for different data spacing. The trapezoidal rule has been used to perform integration, whereas Newton's divided difference handles the inconsistent data points. The whole process of numerical integration has been automated in Python programming language. The developed code is tested against two example problems, and the results obtained agree with the one shown in the literature.